Anomalous current transients in organic field-effect transistors - Sharma, Abhinav; Mathijssen, Simon G. J.; Cramer, T.; Kemerink, Martijn; Leeuw, Dago M. de; Bobbert, Peter A. (Applied physics letters, 2010)
Here we study the origin of the gate bias-stress effect in organic ppp-type transistors. Based on water-mediated exchange between holes in the semiconductor and protons in the gate dielectric, we predict anomalous current transients for a non-constant gate bias, while ensuring accumulation. When applying a strongly negative gate bias followed by a less negative bias a back-transfer of protons to holes and an increase of the current is expected. We verify this counterintuitive behavior experimentally and can quantitatively model the transients with the same parameters as used to describe the threshold voltage shift.
Gesehen am 12.12.2019